Dampak Implementasi Rekam Medis Elektronik terhadap Mutu Pelayanan Rumah Sakit - Aditya Kurniawan; Saryadi Saryadi; Liss Dyah Dewi Arini (Jurnal Ilmiah Kedokteran dan Kesehatan, 2025)
The implementation of Electronic Medical Records (EMR) has become a pivotal advancement in enhancing hospital service quality. This study aims to analyze the impact of EMR implementation on the quality of healthcare services by comparing the conditions before and after its adoption. Through a comprehensive literature review of peer-reviewed articles published in the last ten years indexed by Scopus, Web of Science, and Sinta 1 and 2, this research identifies key improvements in efficiency, data accuracy, patient safety, and user satisfaction. The findings reveal that EMR significantly reduces medical errors, shortens patient waiting times, and improves interdisciplinary collaboration. However, challenges such as infrastructure readiness and human resource adaptation remain critical barriers. The study concludes that strategic planning and continuous training are essential to maximize the benefits of EMR for sustainable service quality enhancement in hospitals.